Moral Values in Western and Indonesian Stories: A Research on the Stories for the Ninth Grade of Junior High School - Eros Meilina Sofa (Journal of English Education and Teaching, 2020)
Moral value is one of the parts in a story which can be learned and adapted by students. Stories are classified into several kinds depending on their contents. There are two classifications of stories taught in the ninth grade of Junior High School: Indonesian and western stories, and both of them creates different characteristics and teaching practice of the stories, as well as their moral values. This case study investigated the Indonesian and western stories used in the ninth grade of Junior High School, as well as the moral values conveyed in the stories and how the teachers teach the students those different moral values. This study analyzed the stories contained in the ninth graders’ textbook and interviewed three teachers from different junior high schools related to their teaching practice. After analyzing the data, it was revealed that there are only two Indonesian stories and four western stories as the material in the ninth grade of junior high school’s textbook; those Indonesian and western stories have different characteristics of moral values in several aspects as the result of the classification of the stories; and the different classification of the stories bear the different treatments in teaching moral values contained in the stories.